Who is to Blame for the Dearth of Viable Local Journals in Africa? A Desperate Call - Jacob Owusu Sarfo (Centre for Behaviour and Wellness Advocacy, 2019)
Generally, there is an assertion that Africa as a continent provides the world with relatively small research output. This perception seems valid since Africa accounts only for 2 % of the global research output (Moahi, 2012). Furthermore, most of these studies are published in foreign journals by African authors. This practice is due to several reasons. Firstly, some researchers prefer foreign journals to local ones due to the perceived prestige of publishing abroad (Alemna, 1996). Secondly, they choose foreign journals because of their swift review process, and high visibility through international abstracting and indexing (Tarkang, Bain, 2019). Although these factors may seem harmless to the average African researchers and academics, they may affect the degree of quality manuscripts submitted to existing local journals and journal viability rate in Africa.